Textbook Of Laser And Light Dermatology In The Asian Skin. (WSPC, 2011)
Laser has been used in dermatology for over four decades. The concept of selective photothermolysis has transformed our understanding of laser tissue interactions, and there has been an explosive interest in laser treatment for both skin diseases and aest.